2005
DOI: 10.1111/j.1743-6109.2005.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and Interpersonal Dimensions of Sexual Function and Dysfunction

Abstract: Introduction There are limited outcome data on the efficacy of psychological interventions for male and female sexual dysfunction and the role of innovative combined treatment paradigms. Aim To highlight the salient psychological and interpersonal issues contributing to sexual health and dysfunction; to offer a four-tiered paradigm for understanding the evolution and maintenance of sexual symptoms; and to offer recommendation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
98
0
10

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 212 publications
(112 citation statements)
references
References 34 publications
4
98
0
10
Order By: Relevance
“…Not only is depression a risk factor for sexual dysfunction [20], the medications associated with treating it, particularly selective serotonin reuptake inhibitors, are associated with sexual dysfunctions such as anorgasmia, erectile dysfunction, and diminished libido that may persist after medication use is discontinued [21].…”
Section: Psychologicalmentioning
confidence: 99%
“…Not only is depression a risk factor for sexual dysfunction [20], the medications associated with treating it, particularly selective serotonin reuptake inhibitors, are associated with sexual dysfunctions such as anorgasmia, erectile dysfunction, and diminished libido that may persist after medication use is discontinued [21].…”
Section: Psychologicalmentioning
confidence: 99%
“…By itself, orgasmic disorder is a common and often straightforward disorder to treat with a number of standard treatment protocols, most notably directed masturbation (Althof et al, 2005;Heiman, 2002;Stinson, 2009). The treatment of orgasmic disorder in the context of two co-morbid sexual dysfunctions, post-traumatic stress disorder, and major depression and in the context of serious abuse, family, relationship and medical problems was not typical and quite challenging-necessitating longterm treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This treatment promotes attitude, thought, and behavior changes and anxiety reduction through exercises such as directed masturbation, sensate focus (i.e., exercises developed by Masters and Johnson to assist couples experiencing sexual problems), Kegel exercises, communication skills training, systematic desensitization, and sex education (Althof et al, 2005;Heiman, 2002;Stinson, 2009). While ''there are no pharmacological agents proven to be beneficial beyond control,'' several pharmacological agents such as sildenafil, ArginMax, granisetron, and estrogen and testosterone show promise in treating orgasmic dysfunction (Meston, Hull, Levin, Sipski, & Heiman, 2004, p. 242), with sildenafil showing promise with anti-depressant associated orgasmic dysfunction (Nurnberg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A follow-up study of patients treated with Viagra TM revealed that one-quarter of the sample was unable to sustain initial improvements with the drug, due to difficulty resuming or maintaining their sexual relationship (Pallas, Levine, Althof, & Risen, 1999). Although PDE-5 inhibitors may facilitate better erections, they fail to address key individual and/or couple problems (Althof et al, 2005;Perelman, 2005). Strengthening this statement is evidence suggesting that partner satisfaction and involvement are crucial for treatment compliance and long-term use; men with uninvolved partners are more likely to discontinue the use of medical interventions for ED (Montorsi & Althof, 2004;Riley, 2002).…”
mentioning
confidence: 88%